Aktivitas Daya Hambat Ekstrak Etanol Biji Pinang (Areca catechu L.) terhadap Isolat Bakteri Gigi - Meiriza Djohari; Armon Fernando; Annisa Safitri (Fakultas Farmasi Universitas Pancasila, 2020)
Areca nut is traditionally used by the community to strengthen teeth. Areca nuts contain alkaloid, flavonoid, and terpenoid as antibacterials. This study aims to determine the types of dental bacteria resulting from isolates and determine the effect of the administration of ethanol extract of areca nut (Areca catechu L.) on the results of isolates of dental bacteria. Antibacterial activity testing using disc diffusion method with the concentration of areca nut ethanol extract 10%, 20% and 30%. The results showed that bacteria of the tooth are Lactobacillus casei, Branhamella catarrhalis, Streptococcus sp. Ethanol extract of areca nut (Areca catechu L.) is better to inhibit the growth of Lactobacillus casei compared to Branhamella catarrhalis and Streptococcus sp in the medium to weak category. Two Way ANOVA test results on inhibitory zone diameter stated that there were differences between the concentration groups of 10%, 20%, 30%, positive control and negative controls and there were differences in the inhibitory activity of Lactobacillus casei compared to Branhamella catarrhalis and Streptococcus sp but there were no significant differences on the inhibitory activity of Branhamella catarrhalis with Streptococcus sp.